TINJAUAN YURIDIS PERKARA Iá¹ BAT NIKAH SECARA VOLUNTAIR DAN CONTENTIUS DI PENGADILAN AGAMA KEBUMEN - MAHFUD, ALI (Dinamika Hukum, 2019)
The results of the study show that there are only one-sided interests or voluntary claims or claims. Whereas in the claim or contention there is a dispute with another party / parties, which is a minimum of 2 parties. The voluntary lawsuit, there is only one party that submits or is absolutely one party (ex-parte). Whereas in contention there are parties or third parties involved with different interests. The voluntary lawsuit is processed simply and then given a determination. Whereas in the contention case, a contradiction is carried out, such as there are duplicates, and so on, in which each party has the right to be given their respective opportunities to make their own defense or defense in accordance with the established procedures, to produce a court decision. Juridical Review Used by Kebumen Religious Court Judges on the Determination / Decision of Marriage in Voluntary Dan Contentius, namely the basis of consideration of the Kebumen Religious Court in providing the marriage certificate, namely by looking at and examining the legal standing of the applicant to file a marriage certificate in a religious court and Fundamentum Petendi (posita) is the basis or proposition of a lawsuit that contains the events and legal relationship of marriage rights and the reason or purpose in filing a marriage certificate. In addition, the reason for submitting the marriage certificate at the Kebumen Religious Court is not limited to what is mentioned in article 7 paragraph (3) KHI, but also for the purposes of making a child birth certificate and other interests. Keywords: Juridical, Islamic, Voluntary, Contentius Review